الصورة الفنية معيارا نقديا: دراسة في أدوات الناقد - شهيل رياض جباري (Al-Adab Journal, 2019)
term image at the end of nineteenth century and early twentieth century, the artistic use figurative language or Alastarah in the poetry, and promised - any Alsourh- an important element of building the poem, derives its meaning from its context, it should be if in our study of the poem to examine the pictures together ; so that we can uncover deeper than the virtual text meaning of meaning, because the picture - which is all figurative forms as Qdinma- but be the work of the creative force, the trend to study means the trend to the spirit of poetry and its meaning and significance, through the study of capillary action fabric, and Mandy as a structure relationships reveals the interaction of the meaning of the poem and its significance, and this angle shows the importance of the technical picture of the contemporary critic; it and his method, which explores the poem, as well as the position of the poet of fact, one of the important in judging the authenticity of the experiment calibration, the ability of the poet to form in a format that achieves Have fun and experience for those who receive. Literary criticism terminology, concepts and special approach in the picture; we tried in this study to stand at a notably to detect the dimensions and significance monetary tool facilitates the work of the critic in His applied and theoretical exercise on texts.